1978
DOI: 10.1037/0021-9010.63.5.609
|View full text |Cite
|
Sign up to set email alerts
|

A test of Holland's environment formulations.

Abstract: One hundred and eighty-one occupations, for which reinforcer rating data were available, were classified into the six Holland environment models. Mean reinforcer scale scores were found to differ significantly among the six environments on 17 reinforcer scales, on 12 of which there were significant pairwise differences. Comparison of hypothesized and observed rank orderings of the six environments showed significant agreement on eight reinforcer scales. Comparison of mean score differences between alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…In addition, at least for cognitive measures, test score means increase as job complexity increases. With respect to occupational interests, Holland's model of interests has been linked to the job components of the PAQ (Hyland & Muchinsky, 1991;Rounds, Shubsachs, Dawis, & Lofquist, 1978).…”
Section: Job Component Validitymentioning
confidence: 99%
“…In addition, at least for cognitive measures, test score means increase as job complexity increases. With respect to occupational interests, Holland's model of interests has been linked to the job components of the PAQ (Hyland & Muchinsky, 1991;Rounds, Shubsachs, Dawis, & Lofquist, 1978).…”
Section: Job Component Validitymentioning
confidence: 99%
“…Indeed, a number of additional applications are evident in the literature, including the areas of occupational reinforcers (Rounds, Shubsachs, Dawis, & Lofquist, 1978), perceptions of vocational counseling roles (Brook, 1979), potential work mobility (Aranya, Jacobson, 81 Shye, 1976), design of work environments (Kenny & Canter, 1981), job analysis and classification (Brown, 1967;Sackett, Cornelius & Carron, 1981;Smith & Siegel, 1967), and career preferences (Soutar & Clarke, 1983). The diversity of these applications bodes well for the future of multidimensional scaling in vocational psychology research.…”
Section: Representations and I-lierarchical Representationsmentioning
confidence: 99%
“…Regarding the Census categories, she demonstrated that they better differentiated Data tasks than the other tasks but were similar to Holland in differentiating People and Things tasks. Finally, in comparison to occupational reinforcer data (comparable to Toenjes & Borgen, 1974;and Rounds et al, 1978) she demonstrated that types and levels could be differentiated by different patterns of reinforcers. In sum, this study was very supportive of Holland's typology illustrating that work activi ties, job requirements, and rewards could account for significant propor tions of variance in the Holland categories.…”
Section: Use Of Information On the Environment's Populationmentioning
confidence: 84%
“…Multiple discriminant function analyses produced the correct ordering of the categories but the shape was not shown to be exactly hexagonal. Rounds, Shubsasch, Dawis, and Lofquist (1978) also examined ORP data on 181 occupations, plus, they included PAQ data in their analyses. They also found mean differences across occupations on the PAQ.…”
Section: Use Of Information On the Environment's Populationmentioning
confidence: 99%
See 1 more Smart Citation